Utilization of Seamless Learning as a Learning Model during Covid-19 Pandemic in Indonesia - Luluk Setyowati (Scope : Journal of English Language Teaching, 2021)
One of the effects of the 2019-20 Coronavirus pandemic is relied on education throughout the world. Education in Indonesia is also affected by the COVID-19 virus. All levels of education from elementary schools to tertiary institutions (universities) both under the Indonesian Ministry of Education and Culture and those under the Indonesian Ministry of Religion are "forced" to learn from home because of face-to-face learning removed to prevent COVID-19 transmission. Under these conditions, the education system can adopt Seamless Learning. Seamless Learning allows students to determine when and where they will learn. This research is a literature study reviewing studies which show that Seamless can now be done to replace traditional systems during pandemic. Seamless Learning can be an option for learning methods that can be applied during the COVID-19 quarantine period. Seamless Learning allows students to learn more independently and does not sacrifice students with certain hours and duration as long as the material is affordable and accessible to students. Students can easily access material and are not limited by certain devices making it easier for students who do not have a computer or laptop.